Spatiotemporal clusters of primary and secondary syphilis cases in south China: an observational study. (October 2016) - Wong, Ngai Sze; Huang, Shujie; Chen, Lei; Zhao, Peizhen; Tucker, Joseph D; Yang, Li Gang; Goh, Beng Tin; Zheng, Heping; Yang, Bin
Abstract: Background: Although the overall rate of newly reported primary and secondary syphilis cases in Guangdong Province has been decreasing since 2011, incidence in some cities has increased. Location-based intervention is needed for effective resource allocation. We aimed to understand the geographical variations of syphilis epidemiology and detect possible outbreaks and epidemics at county level by spatiotemporal analyses. Methods: In this observational study, we collected demographics, residential location, syphilis staging and diagnosis date of all reported primary and secondary syphilis cases in patients diagnosed and living in 21 cities, which were further subcategorised into 126 smaller counties, in Guangdong Province, China, from 2014 to mid-2015. Spatial distribution of rate of reported primary and secondary cases (in 1000 people) at county level (smaller than city level) were mapped and analysed. We did spatial cluster analyses (Anselin Local Moran's I and Getis-Ord Gi* [hotspot analysis] in ArcGIS) on an annual and monthly basis to detect clusters at county level. Spatiotemporal clusters were also detected by a discrete Poisson model in SaTScan at county level with a 2% population window and 20% temporal window. Institutional review board approval was obtained from the Guangdong Provincial Center for Skin Diseases and STI Control, China. Findings: 18 102 newly reported primary and secondary syphilis cases in patients living in Guangdong Province were analysed. At diagnosis, median age was 39 years (IQR 28–54), and 10 383 (57%) were male individuals. 16 of 126 counties were consistently identified in all methods to have a higher rate of reported cases than expected spatiotemporally, which lasted for 1–5 months. At city level, two cities contained more than half of the counties with clusters. They were also the cities that had rising trends in the incidence of syphilis between 2006 and 2014. Another three cities had a declining syphilis rate, but clusters were detected in one to two counties. Interpretation: Geographical variation and occasional outbreaks even in places with relatively good epidemic control in cities were observed. Spatiotemporal cluster detection methods can be used to focus provincial syphilis control programmes. Funding: None. NSW was supported byGuangdong Provincial Center for Skin Diseases and STI Control and the South China-UNC STD Research Training Center grant (FIC1D43TW009532-01), SESH R01 (NIAID 1R01AI114310), and the Fogarty International Center.